The effect of bovine colostrum usage on serum immunoglobulins and protein levels in basketball players - Ali Kıvrak; Gurkan Ucar (Türk Spor ve Egzersiz Dergisi)
This study was done to investigate the effect of bovine colostrum usage on serum immunoglobulins and protein levels in basketball players. 24 male basketball players from students at Physical Education and Sports in Selcuk University participated in this study. These players were divided into two groups including a control group of 12 persons and an experimental group of 12 persons. The sportsmen's blood samples were taken for the research three times (at 0th, 30th and 60th days), the serum immunoglobulins (IgG, IgA, IgM, IgE) and the proteins (Albumin, Globulin, Total Protein) were analyzed using standard methods. Moreover, the statistical analyses were done for the experimental and control groups in the basketball players with the SPSS 15 program and evaluated as well. When considered the results, it was determined that there were increases in the average amounts of Serum IgG, IgE, Globulin, Total Protein. However, a significant decrease was found in the Serum IgM. And it was found out that there were differences in the globulin amount and the total protein values (P lt;0.05) between the control and experimental groups using colostrum. In conclusion, it has been suggested that future researches on colostrum will be suitable for various sports branches and different age groups considering especially sportsmen' criteria such as immunity, regeneration, performance. Thus, the sportsmen will benefit from the outstanding characteristics of colostrum at a maximum level; the success will be achieved more in this way.